The essence of fair remuneration in the light of new concepts of human capital management of an employees of the company - Leputa, Natalia (SPC Journal of Social Sciences, 2020)
In the following article the author discusses the basic terminology used to understand the concept of fair remuneration. It will address issues such as capital, human capital and the history of their creation, as well as the perception and distribution of remuneration by type and func-tion. Particular attention is paid to fair remuneration and ways of increasing an employee's human capital.Â Â